Strict justification of the fourier method in boundary-value problems of the theory of elasticity for a symmetrically loaded transversally isotropic oblate spheroid and its application to a hollow spheroid - Nikolaev, Oleksii Georhiiovych; Krainychenko, Alina Sergiivna (Національний технічний університет "Харківський політехнічний інститут", 2025)
For the first time, an exact, well-founded solution by the Fourier method of the second axisymmetric boundary value problems of the theory of elasticity in the general formulation for a transversely isotropic oblate spheroid and a space with a spheroidal cavity has been obtained. The fundamental problem of the justification was the problem of estimating from below the modules of the determinants of the resolving systems for the internal and external problems. The indicated estimates were obtained in this work. The complexity of estimating determinants is due to the fact that they depend on nine parameters that are functionally related to each other, and in addition, two of them are included in the arguments of Legendre functions of the first and second kind. The estimates made it possible to formulate and prove theorems about the solvability conditions of the considered boundary value problems in certain classes of functions. The obtained results are applied to the solution of the second boundary value problem for a transversely isotropic oblate spheroid with a spheroidal cavity, the centers and directions of the axes of which coincide. An arbitrary symmetric balanced load is given on the surfaces of the spheroid, which satisfies a certain condition for the convergence of the series of limit functions developed in terms of Legendre functions. Вперше отримано точний обґрунтований розв’язок методом Фур’є осесиметричних(осе) крайових задач теорії пружності в загальній постановці для трансверсально-ізотропного стиснутого сфероїда і простору зі сфероїдальною порожниною. Принциповою проблемою обґрунтування стала проблема оцінки знизу модулів визначників розв’язуваних систем для внутрішньої та зовнішньої задач. У цій роботі отримано вказані оцінки. Складність оцінювання визначників пов’язана з тим, що вони залежать від дев’яти параметрів, які функціонально пов’язані між собою, до того ж, два з них входять в аргументи функцій Лежандра першого і другого роду. Оцінки дали змогу сформулювати і довести теореми про умови розв’язності розглянутих крайових задач у певних класах функцій. Отримані результати застосовано до розв’язання другої крайової задачі для трансверсально-ізотропного стиснутого сфероїда зі сфероїдальною порожниною, центри і напрями осей яких збігаються. На поверхнях сфероїда задано довільне симетричне врівноважене навантаження, яке задовольняє певну умову збіжності рядів граничних функцій, розвинених за функціями Лежандра. Особливістю цієї задачі для трансверсально-ізотропного тіла є неможливість при будь-якій геометрії сфероїдальних поверхонь описати їх однією парою сфероїдальних систем координат.
Строге обґрунтування методу Фур'є в крайових задачах теорії пружності для симетрично навантаженого трансверсально-ізотропного стиснутого сфероїда та його застосування для порожнього сфероїда
Keywords: Fourier method; boundary value problem; transversely isotropic body; oblate spheroid; empty spheroid; justified solution; метод Фур'є; крайова задача; трансверсально-ізотропне тіло; стиснутий сфероїд; порожній сфероїд; обґрунтований розв'язок